Hazard Communication Made Easy: A Checklist Approach to OSHA Compliance - Nelson, Sean M.,; Grubbs, John R., (Government Institutes, 2000)
Using the simple and effective checklist method, this book offers a convenient and efficient way to comply with complicated federal regulations and to help your employees understand the dangers of the hazardous materials in your workplace. Written by the authors of Safety Made Easy, Hazard Communication Made Easy provides you with a practical guide to creating and implementing a complete Hazard Communication Program. You'll find sample forms and documents, a "ready to use" HazCom Program and Training Module, and specific requirements for the most common chemical and physical hazards so you will have all the information you need to customize your individual HazCom programs.